Banking Industry's Commitment to Sustainable Finance Towards Low-Carbon Economy Transformation - Yuliana Indira Islami; Chandra Fitriyani Crisna Mukti; Dorifahtu Afirstantian Maharani; Maria Yovita R. Pandin (Business and Investment Review, 2023)
The purpose of writing this scientific article is to find out that the banking industry's commitment to sustainable finance can lead to a low-carbon economic transition. This article was written using a non-participant observation method. The data taken comes from the Sustainability Report of financial sector institutions on 4 banking industries for the 2022 period. The research design in this article is a descriptive method with a qualitative approach. As for how to analyze the data using the steps: Editing, classification, verification, and the last conclusion. The results of the study of scientific articles show that the four banks as a banking industry use energy to carry out business activities, thereby reducing the impact and operational costs.